Excludentes e atenuantes da responsabilidade civil em pesquisas envolvendo seres humanos à luz da bioética e das teorias do risco e do nexo de causalidade - Aguiar , Renaud Ponte (2024)
potential to cause harm to participants in clinical trials and other forms of scientific research, even if limited to personal information intended for databases. In Brazil, scientific research of this nature is regulated by resolutions of the National Health Council, even in investigations carried out within the scope of the Human Sciences. An analysis of these documents shows that the civil liability of researchers and research-promoting institutions has the extent of the damage as a criterion for establishing the amount of compensation. Since it is an objective liability, based on the Theory of Risk, there is an apparent exclusion from the application of mitigating factors or exclusions from the duty to repair damages. However, even though this criterion is also the general rule in Brazilian Civil Law, there are situations in which liability is modulated based on the degree of fault and even the application of other mitigating factors and exclusions from the duty to repair damages. Since there is no provision for these exclusions and mitigating factors in the specific legislation, the question arises as to whether they can be applied in a way that does not harm the fundamental rights and guarantees of participants, as well as the dignity of the human person. The analysis was based on the perception that we live in a risk society, as evidenced by Ulrich Beck, in which we must compulsorily live with risks, seeking, if not to completely eliminate, at least to minimize the impacts and damages caused by them. This perspective was analyzed based on principled Bioethics, considering the autonomy of will, however, taking into account that this approach is insufficient to explain such a conception in its entirety, especially when a context focused on underdeveloped or developing countries is assumed, as is the case of Brazil, and that, therefore, the considerations of Intervention Bioethics are important. Having highlighted the controversial points of the legislation in force, applied to scientific research, in light of the risk society and Bioethics, after analyzing the adequacy of the environment and the bond of necessity, in accordance with Robert Alexy's postulate of balancing, possible ways to mitigate risks in scientific research were pointed out. As conclusions, the possibility of applying mitigating and excluding civil liability in research involving human beings is defended, but in exceptional situations, respecting the autonomy of will and protecting vulnerable groups. Also, the need to establish mandatory insurance for research with moderate to high risk was highlighted